The Digital Gender Gap in Teacher Education: The TPACK Framework for the 21st Century - Isabel María Gómez-Trigueros; Cristina Yáñez de Aldecoa (MDPI AG, 2021)
The main goal of this research is to explore whether there are any differences by gender regarding the Digital Competence of Teachers (DCT), both in-training and in-service. Simultaneously, the specific goals of the research are to analyse which are the methodologies, including technological, that are being implemented in university classrooms and to evaluate possible new interventions to reduce the digital gender gap. This study is exploratory and descriptive. It relies upon three instruments that have been validated by experts: a questionnaire to collect teachers' in-training perception, a second questionnaire to show in-service teachers' perception regarding their knowledge of technologies, and a rubric to analyse in-service teachers' self-perception regarding methodologies that employ technology. Over three academic years, data were collected from a sample of 914 trainee teachers and 194 professors from several Spanish universities. The results show that, concerning the teaching task, compared to men, the female participants have a very poor self-perception in terms of their Digital Teaching Competence, as well as a lower predisposition towards technologies. We conclude by emphasising the need to transform teaching methodologies in initial teacher education by means of the correct inclusion of ICT tools.